Lean Production Supply Chain and QFD-Analysis in the Process of Healthcare - Nikolaeva, Alena (International Journal of Supply Chain Management, 2018)
The research examines the process of providing medical care to patients, including patients with self-referrals (patients without referral), in the planning and diagnostic department and the trauma department of the city clinical hospital. The aim of the research is to determine the percentage of refusals of